2018
DOI: 10.1038/s41598-018-35385-5
|View full text |Cite
|
Sign up to set email alerts
|

Roles of oxides of nitrogen on quality enhancement of soybean sprout during hydroponic production using plasma discharged water recycling technology

Abstract: This study was performed to assess the effect of plasma-discharged water recycling technology as irrigation water on soybean sprout production. Two different types of irrigation water were used individually for cultivation, including plasma discharged water as a source of oxides of nitrogen and tap water, irrigation water was recycled for every 30 minutes. Plasma discharged irrigation water reduced overall 4.3 log CFU/ml aerobic microbe and 7.0 log CFU/ml of artificially inoculated S. Typhimurium within 5 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Thus, the enhancement of water absorption can trigger faster germination and earlier seedling vigor by regulating endogenous hormones and hydrolytic enzymes during imbibition and sequentially supplying nutrients to an actively growing embryo ( Li et al, 2014 ; Stolárik et al, 2015 ; Chen et al, 2016 ; Ji et al, 2016 ; Guo et al, 2017 ; Sadhu et al, 2017 ). Additionally, plasma-induced ROS, RNS, and UV can lead to better seed germination and seedling establishment under stressful conditions as follows: 1) reduce infection with pathogenic microorganisms in germinating seeds or growing plants ( Selcuk et al, 2008 ; Filatova et al, 2014 ; Jiang et al, 2014b ; Zahoranová et al, 2016 ; Ono et al, 2017 ; Lee et al, 2019 ), 2) regulate ROS homeostasis through the antioxidant machinery of plants ( Yin et al, 2005 ; Šerá et al, 2010 ; Henselová et al, 2012 ; Bußler et al, 2015 ; Li et al, 2015 ; Chen et al, 2016 ; Ji et al, 2016 ; Guo et al, 2017 ; Li et al, 2017 ; Zhang et al, 2017 ), and 3) activate other defense-related responses in plant cells ( Iranbakhsh et al, 2017 ; Iranbakhsh et al, 2018 ). Many studies have shown that the application of exogenous ROS, RNS, or UV radiation has similar effects on seeds, thus resulting in an enhanced stress tolerance before stress events ( Antoniou et al, 2016 ; Thomas and Puthur, 2017 ).…”
Section: Combined Plasma Effects On Crop Stress Tolerancementioning
confidence: 99%
“…Thus, the enhancement of water absorption can trigger faster germination and earlier seedling vigor by regulating endogenous hormones and hydrolytic enzymes during imbibition and sequentially supplying nutrients to an actively growing embryo ( Li et al, 2014 ; Stolárik et al, 2015 ; Chen et al, 2016 ; Ji et al, 2016 ; Guo et al, 2017 ; Sadhu et al, 2017 ). Additionally, plasma-induced ROS, RNS, and UV can lead to better seed germination and seedling establishment under stressful conditions as follows: 1) reduce infection with pathogenic microorganisms in germinating seeds or growing plants ( Selcuk et al, 2008 ; Filatova et al, 2014 ; Jiang et al, 2014b ; Zahoranová et al, 2016 ; Ono et al, 2017 ; Lee et al, 2019 ), 2) regulate ROS homeostasis through the antioxidant machinery of plants ( Yin et al, 2005 ; Šerá et al, 2010 ; Henselová et al, 2012 ; Bußler et al, 2015 ; Li et al, 2015 ; Chen et al, 2016 ; Ji et al, 2016 ; Guo et al, 2017 ; Li et al, 2017 ; Zhang et al, 2017 ), and 3) activate other defense-related responses in plant cells ( Iranbakhsh et al, 2017 ; Iranbakhsh et al, 2018 ). Many studies have shown that the application of exogenous ROS, RNS, or UV radiation has similar effects on seeds, thus resulting in an enhanced stress tolerance before stress events ( Antoniou et al, 2016 ; Thomas and Puthur, 2017 ).…”
Section: Combined Plasma Effects On Crop Stress Tolerancementioning
confidence: 99%
“…This pre-planting technique can improve radicle emergence, germination speed, and seedling establishment by changing the metabolic activity of seeds (Ghassemi-Golezani et al, 2016;Damalas et al, 2019;Zulfiqar et al, 2022). The combination of CP with hydropriming resulted in smoothing of the seed surface (Wang et al, 2017), the regulation of osmotic salts, and the alteration of the subsequent process of water uptake (Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The decontamination of soybean seeds contaminated with bacteria using PAW was reported by Lee et al [ 44 ]. PAW reduced the overall 4.3-log CFU/mL amount of aerobic microbes and 7.0-log CFU/mL of artificially inoculated Salmonella Typhimurium within 5 min and 2 min, respectively.…”
Section: Surface Seed and Sprout Decontaminationmentioning
confidence: 99%
“…In [ 44 ], the authors also observed an increase in ascorbate, asparagine and γ-aminobutyric acid (GABA), and followed the development of cotyledon and hypocotyl in germinating soybean seed of soybean from the 1st to the 4th day of cultivation. In Zhou et al [ 58 ], the authors applied PAW on mung beans and reported that the high concentration of ROS might contribute to the chapping of seed coat, which improved its absorption of water and nutrients.…”
Section: Seed Germinationmentioning
confidence: 99%
See 1 more Smart Citation